Controversies Surrounding Clostridium difficile Infection in Infants and Young Children - Maribeth R. Nicholson; Isaac P. Thomsen; Kathryn M. Edwards (MDPI AG, 2014)
Clostridium difficile is a frequent cause of antibiotic-associated diarrhea in adults and older children. However, as many as 80% of infants can be asymptomatically colonized. The reasons for this have not been well established but are believed to be due to differences in toxin receptors or toxin internalization. Determining which children who test positive for C. difficile warrant treatment is exceedingly difficult, especially in the setting of increased rates of detection and the rising risk of disease in children lacking classic risk factors for C. difficile.